2016
DOI: 10.1051/e3sconf/20160801050
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and density models for copper electrorefining electrolytes

Abstract: Abstract. Viscosity and density are highly important physicochemical properties of copper electrolyte since they affect the purity of cathode copper and energy consumption [1,2] affecting the mass and heat transfer conditions in the cell [3]. Increasing viscosity and density decreases the rate in which the anode slime falls to the bottom of the cell [4,5] and lowers the diffusion coefficient of cupric ion (DCu2+) [6]. Decreasing the falling rate of anode slime increases movement of the slime to other direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…5). The factors of Model L and LPD also showed that the impact of the viscosity value origin (Kalliomäki et al (2017) vs. Price and Davenport (1981)) had only a minor effect on the diffusion coefficient equation constructed. These results indicate that increasing concentrations of Cu, Ni, H2SO4 and As decreases the diffusion coefficient value, while an increase in temperature leads to a direct increase in DCu(II).…”
Section: Limiting Current Density Model and Diffusion Coefficient Modelsmentioning
confidence: 95%
See 3 more Smart Citations
“…5). The factors of Model L and LPD also showed that the impact of the viscosity value origin (Kalliomäki et al (2017) vs. Price and Davenport (1981)) had only a minor effect on the diffusion coefficient equation constructed. These results indicate that increasing concentrations of Cu, Ni, H2SO4 and As decreases the diffusion coefficient value, while an increase in temperature leads to a direct increase in DCu(II).…”
Section: Limiting Current Density Model and Diffusion Coefficient Modelsmentioning
confidence: 95%
“…1), respectively. Calculation of the DCu(II) for Models K, M and L utilized the viscosities previously measured by Kalliomäki et al (2017) (Eq. 4) and Model LPD used the viscosities outlined by Price and Davenport (Price and Davenport, 1981).…”
Section: Limiting Current Density Model and Diffusion Coefficient Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of elements obtained after the refinement is 16767. The main parameters of the model are shown in Table 1, in which the density and viscosity of the electrolyte are given in the literature [8][9][10] . The geometric model was meshed and solved to analyze the concentration distribution in the model.…”
Section: Geometric Model and Main Parametersmentioning
confidence: 99%